The Influence of Academic Self-Efficacy and Peers on Economic Academic Achievement: The Role of Learning Motivation as a Mediating Variable - Tsabitah, Okta Emillia; Pamungkas, Heni Purwa (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study is designed to examine the influence of academic self-efficacy and peers on economic academic achievement through learning motivation as a mediating variable in class X students of SMA Negeri 14 Surabaya. This research includes causal associative research with a quantitative approach. A total of 179 research samples were selected using simple random sampling techniques from a total population of 324 students. The research data was obtained from the results of the questionnaire and the Semester-end Summative (SAS) score of the economic odd economic year 2024/2025 which was analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) technique assisted by SmartPLS software. The findings of the study indicate that academic self-efficacy and peers have a positive and significant effect directly on economic academic achievement, and indirectly academic self-efficacy and peers have a positive and significant effect on economic academic achievement through learning motivation. These findings confirm the importance of academic self-efficacy and peers in increasing students' learning motivation and economic academic achievement